Enacting inclusivity in the preparation of emerging scholars: A response to programme reform in higher education. Issue 1 (1st March 2020) - Stewart, Saran; Haynes, Chayla; Deal, Kristin
Abstract: This article explores how three doctoral candidates enrolled in the discipline of Higher Education gained an understanding of social justice, equity-mindedness and diversity in the academy. Prior to the admission of these three students, two faculty members had reformed the doctoral programme to align it with the principles of inclusive pedagogy. They created a conceptual framework for the redesign of the programme's mission, curriculum and pedagogy. Echoing an article that those faculty members wrote about the programme, the authors use a collaborative autoethnographic approach to share their experiences of the programme. Just as the faculty members engaged in a fictitious dialogue with their source of inspiration, bell hooks, the authors engage in a conversation with the programme chair about their pursuit of education as the practice of freedom.